Integrated fluorescent cytology with nano‐biologics in peritoneally disseminated gastric cancer. Issue 10 (23rd September 2018) - Watanabe, Megumi; Kagawa, Shunsuke; Kuwada, Kazuya; Hashimoto, Yuuri; Shigeyasu, Kunitoshi; Ishida, Michihiro; Sakamoto, Shuichi; Ito, Atene; Kikuchi, Satoru; Kuroda, Shinji; Kishimoto, Hiroyuki; Tomida, Shuta; et al.
Abstract : Gastric cancer patients positive for peritoneal cytology are at increased risk of tumor recurrence, but although a certain proportion of cytology‐positive patients relapse rapidly with aggressive progression, others survive longer with conventional chemotherapies. This heterogeneity makes it difficult to stratify patients for more intensive therapy and poses a substantial challenge for the implementation of precision medicine. We developed a new approach to identify biologically malignant subpopulations in cytology‐positive gastric cancer patients, using a green fluorescent protein (GFP)‐expressing attenuated adenovirus in which the telomerase promoter regulates viral replication (TelomeScan, OBP‐401). The fluorescence emitted from TelomeScan‐positive cells was successfully quantified using a multi‐mode microplate reader. We then analyzed clinical peritoneal washes obtained from 68 gastric cancer patients and found that patients positive for TelomeScan had a significantly worse prognosis. In 21 cytology‐positive patients, the median survival time of those who were TelomeScan positive (235 days) was significantly shorter than that for those who were TelomeScan negative (671 days; P = 0.0062). This fluorescent virus‐guided cytology detects biologically malignant cancer cells from the peritoneal washes of gastric cancer patients and may thus be useful for both therapy stratification and precision medicine approaches based on genetic profiling of disseminated cells. Abstract : The unique TelomeScan‐guided cytology detects biologically malignant cancer cells from the peritoneal washes of gastric cancer patients. It assists in identifying a subpopulation of patients with particularly poor prognosis among those who are cytology positive on conventional methods.